1993
DOI: 10.1002/ajpa.1330920306
|View full text |Cite
|
Sign up to set email alerts
|

Torso morphology and locomotion in Proconsul nyanzae

Abstract: A new partial skeleton of Proconsul nyanzae from Mfangano Island, Kenya (KNM-MW 13142) includes five lumbar vertebrae, a partial sacrum, and nearly complete hipbone. Until recently, little was known of the axial and pelvic skeletons of Proconsul, or any early Miocene hominoid. Because torso morphology directly reflects locomotor behavior, these elements provide important new information about posture and locomotion of P. nyanzae. Two basic patterns of locomotor behavior and corresponding torso morphology exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
338
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(349 citation statements)
references
References 104 publications
(188 reference statements)
9
338
2
Order By: Relevance
“…128 The short lumbar spines of great apes are very stiff and have limited flexion. 201 This differential evolution of human and old world primate lumbar spines suggests a functional purpose for 5 lumbar vertebrae in humans, not an evolutionary failure.…”
Section: Structural Evolution In the Lumbar Spinementioning
confidence: 99%
“…128 The short lumbar spines of great apes are very stiff and have limited flexion. 201 This differential evolution of human and old world primate lumbar spines suggests a functional purpose for 5 lumbar vertebrae in humans, not an evolutionary failure.…”
Section: Structural Evolution In the Lumbar Spinementioning
confidence: 99%
“…The conclusion to be drawn from the morphology of proconsulids is that they were arboreal climbers, moving on the tops of branches, but they were not habitual leapers rather moved slowly and powerfully in the trees. They were mainly fruit eaters with body sizes varying from 9-11 kg to 63-83 kg, from siamang size to larger than chimpanzees, and some degree of terrestrial activity is indicated, particularly for the larger species, which were as big as chimpanzees or even bigger (Le Gros Clark and Leakey, 1951;Napier and Davis, 1959;Napier, 1960;Andrews, 1978Andrews, , 1992Walker et al, , 1993Rose, 1983Rose, , 1984Beard et al, 1986;Gebo et al, 1988;Rafferty, 1988;Lewis, 1989;Teaford, 1988, 1989;Ward, 1993;Begun et al, 1994;Teaford, 1994;Rafferty et al, 1995;Ward et al, 1995;Harrison, 2002;Gebo et al, 2009). Primates at the upper end of the size range and living in woodland (non-forest) environments, must have been partly terrestrial, as in chimpanzees and gorillas today, for they were too large to move easily between arboreal pathways.…”
Section: Morphology Of Fossil Apesmentioning
confidence: 99%
“…Clearly, primates of this size, living in relatively open canopy woodlands, would have had to spend part of their time on the ground. The thick enamel of their teeth suggest a harder, coarser fruit and nut diet compared with proconsulids (Tekkaya, 1974;Alpagut et al, 1990Alpagut et al, , 1996Teaford, 1988Teaford, , 1991Harrison, 1992;McCrossin and Benefit, 1997;McCrossin et al, 1998;Nakatsukasa et al, 1998Nakatsukasa et al, , 2007Begun and Güleç, 1998;King et al, 1999;Ishida et al, 1999Ishida et al, , 2004Ward, 1993;Ward et al, 1995;Kelley et al, 2000Kelley et al, , 2002Kelley et al, , 2008Kelley, 2002Kelley, , 2008Ungar, 2007;Ersoy et al, 2008;Nakatsukasa, 2008).…”
Section: Morphology Of Fossil Apesmentioning
confidence: 99%
“…Recently published 40 Ar/ 39 Ar dates indicate an age of 20.6 Ma (Gebo et al, 1997), although Pickford (1998) and Pickford et al (1999Pickford et al ( , 2003 claim that Moroto may be younger, possibly late early Miocene (~17.0-17.5 Ma) or early middle Miocene, based on faunal correlations. Morotopithecus is recognized as a stem hominoid based on the presence of synapomorphies of the postcranium (particularly the lumbar vertebrae) that link it with extant hominoids (Ward, 1993;Sanders and Bodenbender, 1994;Gebo et al, 1997; and Benefit, 1994;Ward et al, 1999;Ward and Duren, 2002). During MN 5 and basal MN 6 (~14-17 Ma), Griphopithecus, a primitive hominoid similar in dental morphology and probably closely related to Equatorius, expanded its range into Eurasia, soon after the arrival of pliopithecids (Andrews et al, 1996;Heizmann and Begun, 2001).…”
Section: Introductionmentioning
confidence: 99%